2001
DOI: 10.1097/00002030-200108170-00009
|View full text |Cite
|
Sign up to set email alerts
|

Simplification with abacavir-based triple nucleoside therapy versus continued protease inhibitor-based highly active antiretroviral therapy in HIV-1-infected patients with undetectable plasma HIV-1 RNA

Abstract: The replacement of PI by abacavir in a triple combination regimen following prolonged suppression of plasma HIV-1 RNA provides continued virological suppression, significant improvements in lipid abnormalities and enhanced ease of dosing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
69
2
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(78 citation statements)
references
References 18 publications
6
69
2
1
Order By: Relevance
“…In this study, the TZV regimen was well tolerated over 96 weeks and the safety profile did not change over time. Thus, the incidence of adverse events in the TZV group at 96 weeks was comparable to that reported in other studies that have evaluated ABC/3TC/ZDV over 48 weeks [13,14]. The greater elevation of serum lactate in the d4T/3TC/NFV group is consistent with earlier studies showing d4T to be associated with most NRTI-related cases of hyperlactataemia, which may be related to the greater mitochondrial toxicity profile of this thymidine compared to other NRTIs [30].…”
Section: Discussionsupporting
confidence: 86%
“…In this study, the TZV regimen was well tolerated over 96 weeks and the safety profile did not change over time. Thus, the incidence of adverse events in the TZV group at 96 weeks was comparable to that reported in other studies that have evaluated ABC/3TC/ZDV over 48 weeks [13,14]. The greater elevation of serum lactate in the d4T/3TC/NFV group is consistent with earlier studies showing d4T to be associated with most NRTI-related cases of hyperlactataemia, which may be related to the greater mitochondrial toxicity profile of this thymidine compared to other NRTIs [30].…”
Section: Discussionsupporting
confidence: 86%
“…With regard to the major side effects associated with the use of PIs, alternative therapies have been proposed to replace the PIs with abacavir (42,43) or by the NNRTI nevirapine (44 -46) or efavirenz (47,48). These approaches appear successful to control HIV infection, particularly with the NNRTI (43).…”
mentioning
confidence: 99%
“…Although such a measurement is subjective, the low number of daily pills and the good tolerability of the simplified regimen are important features of a long-term therapeutic strategy and may help to maintain antiviral efficacy. This is confirmed by additional randomized studies examining the switch from PIs to either abacavir or nevirapine, which have reported easier adherence and improved quality of life for patients who switched [18,33].…”
Section: Discussionmentioning
confidence: 62%